Influence of Non-Projected Materials on the Academic Performance of Preschool Children in Nyamaiya Division, Nyamira County, Kenya - Risper N. Nyang’au,; Dr. Godfrey Ayaga, (IJRDO- Journal of Educational Research, 2020)
The need to improve the transition and enrollment rate for pre-primary children is a matter of global concern for all education stakeholders. Thus, the purpose of the study was to assess influence of non-projected materials on the academic performance of preschool children in Nyamaiya Division, Nyamira County, Kenya. The information provided by this research will benefit policymakers, community members and academicians. It adopted descriptive research design with a target population of 41,668 pre-primary school teachers and pupils. The sample size of 102 pre-primary school teachers and 216 pupils which was determined using the Krejcie & Morgan table (1970). The researcher collected data using questionnaires and the instruments was validated by the supervisors. Reliability of the instruments was determined through a pilot study, thereafter; Cronbach alpha coefficients was used. Quantitative data was analyzed using descriptive statistics, and be presented in graph and tables.